Nondogmatic Social Discounting - Millner, Antony (American Economic Review, 2020)
The long-run social discount rate has an enormous effect on the value of climate mitigation, infrastructure projects, and other long-term public policies. Its value is however highly contested, in part because of normative disagreements about social time preferences. I develop a theory of “nondogmatic” social planners, who are insecure in their current normative judgments and entertain the possibility that they may change. Although each nondogmatic planner advocates an idiosyncratic theory of intertemporal social welfare, all such planners agree on the long-run social discount rate. Nondogmatism thus goes some way toward resolving normative disagreements, especially for long-term public projects. (JEL D61, H43)